1989
DOI: 10.1161/01.str.20.9.1226
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal network disturbance after focal ischemia in rats.

Abstract: We studied functional disturbances following left middle cerebral artery occlusion in rats. Neuronal function was evaluated by [ 14 C]2-deoxyglucose autoradiography 1 day after occlusion. We analyzed the mechanisms of change in glucose utilization outside the infarct using Fink-Heimer silver impregnation, axonal transport of wheat germ agglutinin-conjugatedhorseradish peroxidase, and succinate dehydrogenase histochemistry. One day after occlusion, glucose utilization was remarkably reduced in the areas surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
38
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 48 publications
10
38
1
Order By: Relevance
“…Likewise, transient changes of cholin, creatin, and N-acetylaspartate have been detected within the unaffected hemisphere during the first 12 h in a similar experimental model (Abe et al, 2000). Kataoka et al (1989) confirmed the presence of neuronal degeneration in several cortical areas of the contralateral hemisphere, 5 days after the onset.…”
Section: Introductionsupporting
confidence: 59%
“…Likewise, transient changes of cholin, creatin, and N-acetylaspartate have been detected within the unaffected hemisphere during the first 12 h in a similar experimental model (Abe et al, 2000). Kataoka et al (1989) confirmed the presence of neuronal degeneration in several cortical areas of the contralateral hemisphere, 5 days after the onset.…”
Section: Introductionsupporting
confidence: 59%
“…The disturbance of somatosensory transmis sion observed 1 day after occlusion is attributable to acute ischemic elimination of corticofugal facilita tive activities upon the thalamic relay neurons. This has been suggested by our previous deoxyglucose study (Kataoka et al, 1989). Transient recovery of somatosensory transmission occurred 4-7 days af ter infarct and preceded subsequent depression ob served on the 14th postocclusion day.…”
Section: ----------------------------------------------supporting
confidence: 69%
“…The Fink-Heimer silver impregnation method revealed massive terminal degeneration in the ipsi lateral thalamus 4 days after MCA occlusion (Kataoka et al, 1989). In the present study, TTC staining decreased in the ipsilateral thalamus 4 days after MCA occlusion.…”
Section: ----------------------------------------------supporting
confidence: 58%
See 1 more Smart Citation
“…Numerous afferent and efferent cortical projections pass through or end in the infarcted zone, which included part of the somatosensory cortex and lateral striatum. After unilateral middle cerebral artery occlusion in rats, prominent axonal and terminal degeneration has been shown in cortical, striatal, thalamic, and nigral areas adjacent to the infarct (Iizuka et al, 1989;Kataoka et al, 1989). Furthermore, Yam et al (1998) have reported breakdown of axonal cytoskeleton and disruption of axonal transport inside and around the infarct after cerebral ischemia in rats.…”
Section: Restoration Of Ipsilateral Connectivitymentioning
confidence: 99%